Respuesta :
Answer:
the required equation is y = ( -2/3 )x -7
Step-by-step explanation:
Given :-
the line passes through the point ( 0 , -7 )
)and slope of the line is ( -2/3 )
• To form an equation when one point and it's slope is given ,
• To form an equation when one point and it's slope is given , we use ;
• To form an equation when one point and it's slope is given , we use ;( y - y1 ) = m ( x - x1 )
• To form an equation when one point and it's slope is given , we use ;( y - y1 ) = m ( x - x1 )Where , x and y are variables
• To form an equation when one point and it's slope is given , we use ;( y - y1 ) = m ( x - x1 )Where , x and y are variablesand x1 and y1 are the points where the line meet !
• To form an equation when one point and it's slope is given , we use ;( y - y1 ) = m ( x - x1 )Where , x and y are variablesand x1 and y1 are the points where the line meet ! and m is slope of the tangent !!
y1 = -7
x1 = 0
So, putting all the values in the equation we get ,
[tex](y - ( - 7)) = \frac{( -2 )}{3} (x - 0) \\ \\ y + 7 = \frac{ - 2}{3} x \\ \\ 3y + 21 = - 2x \\ \\ 3y = - 2x - 21[/tex]
[tex]3y = - 21 - 2x \\ \\ y = \frac{ - 2}{3} x - \frac{21}{3 } \\ \\ y = \frac{ - 2}{3} x - 7[/tex]
• Slope intercept form of the equation
• Slope intercept form of the equation y = mx + c
• Slope intercept form of the equation y = mx + c Where , m is slope of the line
• Slope intercept form of the equation y = mx + c Where , m is slope of the line and c is y intercept !!
[ also , we can directly put the value of c = -7 and m = ( -2/3 ) from given ]
Hence , here m = (-2/3 ) and c = -7
So, the required equation is y = ( -2/3 )x -7